(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Acridine is classified as a heterocyclic nucleus. It is used in a variety of medications. Acridine nucleus-based therapeutic agents include “quinacrine (antimalarial), acriflavine and proflavine (antiseptics), ethacridine (abortifacient), amsacrine and nitracine (anticancer), and tacrine”. Acridine is produced by extracting the high boiling fraction of coal tar. It is also obtained naturally from plants and sea creatures. “Nucleophilic addition, electrophilic substitution, oxidation, reduction, reductive alkylation, and photoalkylation” are all reactions that acreidine can go through. The current review article summarises acridine’s synthesis, reaction, literature review, and pharmaceutical significance.